Effective Discipline Techniques for Parents - Cassandra Deas; Eboni J. Baugh (EDIS)
FCS-2289, a 3-page fact sheet by Cassandra Deas and Eboni J. Baugh, describes what discipline is, its purpose, and summarizes effective techniques parents can use to discipline their children. Includes references. Published by the UF Department of Family Youth and Community Sciences, November 2008.